Anogenital infection by Chlamydia trachomatis and Neisseria gonorrhoeae in HIV-infected men and women in Salvador, Brazil - Ana Gabriela Travassos; Eveline Xavier-Souza; Eduardo Netto; Eda Vinhaes Dantas; Maiara Timbó; Isabella Nóbrega; Tatiana Haguihara; Júlia Neumayer; Nathalia Lisboa; Maria Angela Soidan; Fábio Ferreira; Carlos Brites (Brazilian Journal of Infectious Diseases, 2016)
Background: Infections caused by Chlamydia trachomatis and Neisseria gonorrhoeae are the most common bacterial sexually transmitted infections throughout the world. These sexually transmitted infections are a growing problem in people living with HIV/AIDS. However, the presence of these agents in extra genital sites, remains poorly studied in our country. The objective of this study was to estimate the prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae anal and genital infection in people living with HIV/AIDS followed in a reference center in Salvador, Brazil. Methods: Cross-sectional study, from June 2013 to June 2015. Proven HIV-infected people attending this reference center were invited. Clinical and epidemiological data were obtained through interview with standardized form. Chlamydia trachomatis and Neisseria gonorrhoeae screening was performed using qPCR (COBAS 4800® Roche). Results: The frequency of positive cases of Chlamydia trachomatis and Neisseria gonorrhoeae was 12.3% in total, 9.2% cases amongst women and 17.1% amongst men. We found 14.0% of positive cases in anus and 3.1% in genital region in men, while 5.6% and 3.6%, in women, respectively. Among men, anal infection was associated with age <29 years (p = 0.033), report of anal intercourse (p = 0.029), pain during anal intercourse (p = 0.028). On the other hand, no association between genital infection and other variables were detected in bivariate analysis. Among women, we detected an association between Chlamydia trachomatis genital infection and age <29 years (p < 0.001), younger age at first sexual intercourse (p = 0.048), pregnancy (p < 0.001), viral load >50 copies/mL (p = 0.020), and no antiretroviral use (p = 0.008). Anal infection in women was associated with age <29 years old (p < 0.001) and pregnancy (p = 0.023), and was not associated with report of anal intercourse (p = 0.485). Conclusion: Missed opportunities for diagnosis in extra genital sites could impact on HIV transmission. The extra genital sites need to be considered to break the HIV and bacterial sexually transmitted infections chain-of-transmission. Keywords: HIV, Chlamydia trachomatis, Neisseria gonorrhoeae, Sexually transmitted infections, Anogenital infections